Pengaruh Budaya Sekolah, Kepemimpinan Instruksional Kepala Sekolah, dan Komitmen Kerja terhadap Kinerja Guru SDN Se-Kecamatan Candi Laras Utara Kabupaten Tapin - Syahminan, Ahmad; Aslamiah, Aslamiah; Suriansyah, Ahmad (LP. Ma'arif Janggan Magetan, 2024)
This study aims to analyze the direct and indirect influence of school culture, principal's instructional leadership, and work commitment on teacher performance in SDN Se-Candi Laras Utara District, Tapin Regency. This research is motivated by initial observations that show the lack of teacher performance. This quantitative research involved a sample of 102 teachers out of a total of 139, selected through Proportional Random Sampling. Data was collected through questionnaires and analyzed using SPSS. The results of the study show that school culture, instructional leadership of school principals and work commitment have a direct and indirect effect on teacher performance. Specifically, the influence of school culture on teacher performance was 0.655, the influence of the principal's instructional leadership on teacher performance was 0.691, the influence of work commitment on teacher performance was 0.731, the influence of school culture on work commitment was 0.508 and the influence of the principal's instructional leadership on work commitment was 0.578. Indirectly, the influence of school culture on teacher performance through work commitment was 0.371, and the influence of the principal's instructional leadership on teacher performance through work commitment was 0.423. It is recommended that principals maintain a positive school culture and instructional leadership while providing relevant professional development programs to maintain teachers' performance and work commitment.